Arsenic and benzo[a]pyrene co-exposure acts synergistically in inducing cancer stem cell-like property and tumorigenesis by epigenetically down-regulating SOCS3 expression. (April 2020) - Wang, Zhishan; Yang, Ping; Xie, Jie; Lin, Hsuan-Pei; Kumagai, Kazuyoshi; Harkema, Jack; Yang, Chengfeng
Highlights: Arsenic and BaP co-exposure acts synergistically in inducing CSC-like property. Arsenic and BaP combined oral exposure acts synergistically in increasing lung tumorigenesis. Arsenic and BaP co-exposure synergizes in causing epigenetic dysregulation. Arsenic and BaP co-exposure down-regulates SOCS3 to enhance Akt and Erk1/2 activation. Abstract: Arsenic and benzo[a]pyrene (BaP) are among the most common environmental carcinogens causing lung cancer. Millions of people are exposed to arsenic through consuming arsenic-contaminated drinking water. High levels of BaP are found in well-done barbecued meat and other food in addition to cigarette smoke. Hence, arsenic and BaP co-exposure in humans is common. However, the combined health effect and the underlying mechanism of arsenic and BaP co-exposure have not been well-understood. In this study we investigate the combined tumorigenic effect of arsenic and BaP co-exposure and the mechanism using both cell culture and mouse models. It was found that arsenic (sodium arsenite, 1.0 µM) and BaP (2.5 µM) co-exposure for 30 weeks synergizes in inducing malignant transformation of immortalized non-tumorigenic human bronchial epithelial cells and cancer stem cell (CSC)-like property to enhance their tumorigenicity. In animal studies, A/J mice were exposed to arsenic in drinking water (sodium arsenite, 20 ppm) starting from gestation day 18. After birth, the dams continuously received arsenic water throughout lactation. At weaning (3 weeks of age), male offspring were exposed to either arsenic alone via drinking the same arsenic water or exposed to arsenic plus BaP. BaP was administered via oral gavage (3 µmol per mouse per week) once a week starting from 3 weeks of age for 8 weeks. All mice were euthanized 34-weeks after the first BaP exposure. It was found that mice in control and arsenic exposure alone group did not develop lung tumors. All mice in BaP exposure alone group developed lung adenomas. However, arsenic and BaP co-exposure synergized in increasing lung tumor multiplicity and tumor burden. Furthermore, 30% of mice in arsenic and BaP co-exposure group also developed lung adenocarcinomas. Mechanistic studies revealed that arsenic and BaP co-exposure does not produce more BPDE-DNA adducts than BaP exposure alone; but acts synergistically in activating aryl hydrocarbon receptor (AhR) to up-regulate the expression of a histone H3 lysine 9 methyltransferase SUV39H1 and increase the level of suppressive H3 lysine 9 dimethylation (H3K9me2), which down-regulates the expression of tumor suppressive SOCS3 leading to enhanced activation of Akt and Erk1/2 to promote cell transformation, CSC-like property and tumorigenesis. Together, these findings suggest that arsenic and BaP co-exposure synergizes in causing epigenetic dysregulation to enhance cell transformation, CSC-like property and tumorigenesis.